Minimizing the Principle Stresses of Powerhoused Rock-Fill Dams Using Control Turbine Running Units: Application of Finite Element Method - Ameen, Ameen Mohammed Salih; Ibrahim, Zainah; Othman, Faridah; Al-Ansari, Nadhir; Yaseen, Zaher Mundher (MDPI, 2018)
This study focuses on improving the safety of embankment dams by considering the effects of vibration due to powerhouse operation on the dam body. The study contains two main parts. In the first part, ANSYS-CFX is used to create the three-dimensional (3D) Finite Volume (FV) model of one vertical Francis turbine unit. The 3D model is run by considering various reservoir conditions and the dimensions of units. The Re-Normalization Group (RNG) k-ε turbulence model is employed, and the physical properties of water and the flow characteristics are defined in the turbine model. In the second phases, a 3D finite element (FE) numerical model for a rock-fill dam is created by using ANSYS®, considering the dam connection with its powerhouse represented by four vertical Francis turbines, foundation, and the upstream reservoir. Changing the upstream water table minimum and maximum water levels, standers earth gravity, fluid-solid interface, hydrostatic pressure, and the soil properties are considered. The dam model runs to cover all possibilities for turbines operating in accordance with the reservoir discharge ranges. In order to minimize stresses in the dam body and increase dam safety, this study optimizes the turbine operating system by integrating turbine and dam models.